Poised to advocate: The pedagogy of the lightning talk in child and youth care education - Jean-Pierre, Johanne; Hassan, Sabrin; Sturge, Asha; Gharabaghi, Kiaras; Lewis, Megan; Bailey, Jonathan; Panitch, Melanie (International Journal of Child, Youth and Family Studies, 2020)
Advocacy is an integral part of child and youth care workers’ roles and a significant component of child and youth care politicized praxis and radical youth work. Drawing from the qualitative data of a mixed-methods study conducted in 2019 at a Canadian metropolitan university, this study seeks to unpack how the pedagogy of the lightning talk can foster advocacy skills to effectively and spontaneously speak out with and on behalf of children, youth, and families in everyday practice when an unforeseen systemic challenge or barrier arises. A purposive sample of 70 undergraduate students was recruited in two child and youth care courses, both of which required students to present a lightning talk. Participants completed an online questionnaire with closed-ended and open-ended questions in order to share their perspectives of the pedagogy of the lightning talk. The findings show that the lightning talk fosters twenty-first century and metacognitive skills and, most importantly, advocacy skills.